Alkyl sulfide main chain polyester resin and powder coating and preparation method thereof

By introducing the main chain structure of alkyl sulfide ether in the polyester resin and regulating the thiodiglycolic acid content, the energy consumption and storage stability of powder coatings are solved, and low-temperature curing of 130°C and excellent paint film leveling is achieved. sex.

CN116333276BActive Publication Date: 2024-12-20JIANGSU DAMIRUI NEW MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211629753.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-19
Publication Date
2024-12-20
Estimated Expiration
2042-12-19

AI Technical Summary

Technical Problem

Powder coatings cannot cure at room temperature, and high-temperature curing consumes a lot of energy, limiting their applications in thermally sensitive surface coatings, and reducing the melting temperature will affect the storage stability of the resin.

Method used

By introducing the main chain structure of alkyl sulfide, the content of thiodiolic acid is regulated, the glass transition temperature is reduced, the melt viscosity of low-temperature curing is achieved, and the thermal stability of the resin is maintained. Polyesters are prepared using specific raw material ratios and process steps. Resin and powder coatings.

Benefits of technology

Low-temperature curing at 130°C is achieved, ensuring the storage stability of the resin and the leveling of the paint film, and optimizing the performance of the powder coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116333276B_ABST
    Figure CN116333276B_ABST
Patent Text Reader

Abstract

The invention discloses a polyester resin containing an alkyl sulfide main chain and a powder coating and a preparation method thereof, wherein the polyester resin internal structural unit contains an alkyl sulfide main chain; the raw material of the polyester resin is composed of the following components by mass: 40-60 parts of aromatic dibasic acid, 30-40 parts of diol, 0.01-2 parts of branching agent, 0-5 parts of acidolysis agent, 0.03-0.2 parts of esterification catalyst, 0.01-1.5 parts of antioxidant, and 0.01-1 parts of curing accelerator. The present invention introduces the alkyl sulfide main chain into the polyester resin for powder coating, and by regulating the content of the alkyl sulfide main chain structure diacid monomer thiodiglycolic acid, the melting temperature is reduced while ensuring the storage stability of the coating. The powder coating prepared by the resin realizes low-temperature curing at 130°C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polyester resin preparation, and particularly relates to a polyester resin containing an alkyl sulfide main chain, and a powder coating prepared based on the resin. Background Art

[0002] As a new type of 100% solid coating, powder coating has become a recognized 4E type coating product that meets the requirements of high production efficiency, excellent coating performance, ecology and economy. However, powder coating cannot be cured into film at room temperature like liquid coating. High temperature can promote the melting and leveling of polymer resin and provide cross-linking reaction of functional groups. High curing temperature and long curing time consume a lot of energy, which is not conducive to resource utilization and energy conservation. The key is to limit the application of powder coating on heat-sensitive surfaces. In order to achieve low-temperature curing of powder coating, the first condition is that the main resin of the coating must be able to melt and level under low temperature conditions. However, when the melting temperature of general resin is lowered, its glass transition temperature will also drop significantly, which will affect the storage stability under room temperature conditions.

[0003] The introduction of ether bonds into polymer chains can improve flexibility. Sulfur has a larger atomic radius than oxygen, so sulfur-containing polymers tend to have better flexibility. When the sulfur-containing functional group is located in the main chain of the polymer, sulfur-containing polymers with different structures can be formed, such as polythioethers, polythioesters, polythiocarbonates, polydisulfide polymers and polysulfites. These polymer materials have excellent thermal and chemical stability, crystallization and optical properties, metal binding ability, photocatalytic properties and self-healing ability. Chinese patent CN111909365B discloses a method for preparing thioether polyesters, which are prepared by ester exchange reaction using thioether prepolymers terminated with mercapto or hydroxyl groups as raw materials. Chen Jun et al. used thiodipropionic acid and resorcinol di(2-hydroxyethyl) ether as the main raw materials to synthesize sulfur-containing biodegradable polyester (Chen Jun, Cheng Zhengzai, Xiong Jing, Wandji Djouonkep Lesly Dasilva, Siegu William Mawuko, Sun Xin, Jia Ruyan, Yuan Beibei, Mario Gauthier. Characterization and properties of biodegradable polyesters based on sulfur-containing monomers [J]. Fine Petrochemicals, 2021, 38(05): 65-69.) Using thiodiglycolic acid as the polymerization modification monomer, the introduction of a flexible CSC sulfide structure in the main chain can improve the flexibility of the main chain and reduce the melt viscosity of the resin. Summary of the invention

[0004] The purpose of the present invention is to provide a polyester resin containing an alkyl sulfide main chain and a powder coating and a preparation method thereof, wherein an alkyl sulfide main chain is introduced into a polyester resin for powder coating, and the content of thiodiglycolic acid, a diacid monomer of the alkyl sulfide main chain structure, is controlled to reduce the melt viscosity under low-temperature curing conditions without significantly decreasing the glass transition temperature (Tg), while ensuring that the resin has good thermal stability. The powder coating prepared from the resin can be cured at a low temperature of 130°C and has excellent storage stability and leveling properties of the paint film.

[0005] To achieve the above object, the present invention adopts the following technical solution:

[0006] A polyester resin containing an alkyl sulfide main chain, wherein the internal structural unit of the polyester resin contains an alkyl sulfide main chain structure; the raw materials of the polyester resin are composed of the following components in parts by mass: 40-60 parts of a dibasic acid, 30-40 parts of a diol, 0.01-2 parts of a branching agent, 0-5 parts of an acidolysis agent, 0.03-0.2 parts of an esterification catalyst, 0.01-1.5 parts of an antioxidant, and 0.01-1 parts of a curing accelerator.

[0007] Preferably, the polyester resin is a carboxyl-terminated polyester resin having an acid value in the range of 20-40 mgKOH / g.

[0008] Preferably, the dibasic acid is one of terephthalic acid and thiodiglycolic acid or a mixture of the two; when it is a mixture of the two, the thiodiglycolic acid accounts for 0-5% of the total amount of the polybasic acid.

[0009] Preferably, the diol is a mixture of one or more of neopentyl glycol, ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 2-methyl-1,3-propylene glycol, 1,3-butylene glycol, 2-methyl-2,4-pentanediol, 2-ethyl-1,3-hexanediol and 1,4-butylene glycol.

[0010] Preferably, the branching agent is a mixture of one or more of trimethylolpropane, trimethylolethane, 1,2,5-pentanetriol and pentaerythritol.

[0011] Preferably, the acidolysis agent is a mixture of one or more of isophthalic acid, adipic acid, trimellitic anhydride and maleic anhydride.

[0012] Preferably, the esterification catalyst is one or a mixture of dibutyltin oxide, tributyltin oxide, dihydroxybutyltin chloride, stannous oxalate, and monobutyltin oxide.

[0013] Preferably, the antioxidant is a mixture of one or more of tris(2,4-di-tert-butylphenyl)phosphite, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and octadecylβ-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate.

[0014] Preferably, the curing accelerator is a mixture of one or more of triphenylphosphine, triphenylethylphosphine bromide, tetraethylammonium bromide, tetrabutylammonium bromide, tetrabutylammonium chloride, and dibutyltin dilaurate.

[0015] Preferably, the solid-liquid transition point temperature of the polyester resin is less than 75.1°C.

[0016] A method for preparing a polyester resin containing an alkyl sulfide main chain comprises the following steps:

[0017] (1) Adding diol, branching agent, esterification catalyst and part of antioxidant into a reactor under nitrogen atmosphere;

[0018] (2) heating, adding aromatic dibasic acid, and stirring evenly;

[0019] (3) heating to start the reaction, then raising the temperature and keeping it warm until the reaction system becomes clear;

[0020] (4) lowering the temperature of the reaction system;

[0021] (5) adding an acidolysis agent, then raising the temperature, keeping the temperature, and continuing the reaction;

[0022] (6) Take samples to analyze the acid value and viscosity. When the qualified indicators are met, add the curing accelerator and the remaining antioxidant, stir and discharge the material.

[0023] Preferably, in step (2), the temperature is raised to 130°C.

[0024] Preferably, in step (3), the temperature is raised to 180°C to start the reaction, and then the temperature is raised to 250°C at a rate of 10-15°C / h. At this temperature, the temperature is maintained until the reaction system becomes clear.

[0025] Preferably, in step (4), when the acid value (AV) detected by sampling reaches 5-20 mgKOH / g, the temperature of the reaction system is reduced to 220°C.

[0026] Preferably, in step (5), the temperature is then raised to 240° C., kept at this temperature for 2 hours, and then the reaction is continued for 2 to 4 hours under a vacuum degree of -0.09 to -0.099 MPa.

[0027] Preferably, in step (6), sampling is performed to analyze the acid value and viscosity, wherein the acid value is controlled at 20-40 mg KOH / g and the viscosity is controlled at 10-50 Pa.s at 180°C. After the indicators are qualified, a curing accelerator and the remaining antioxidant are added, and the material is discharged after stirring for 0.5 h.

[0028] A powder coating, the raw materials of which are composed of the following components in parts by weight: 50-60 parts of a polyester resin containing an alkyl sulfide main chain, 2-4.5 parts of triglycidyl isocyanurate, 10-18 parts of titanium dioxide, 8-16 parts of barium sulfate, 1-2 parts of a leveling agent, 0.5-1 parts of a brightener, and 0.2-0.6 parts of benzoin.

[0029] Preferably, the leveling agent is a GLP503 / 588 leveling agent, the brightening agent is an accelerator BLC701, and the benzoin is benzoyl alcohol ketone.

[0030] A preparation method of a powder coating comprises the following steps: mixing various raw materials in a mixer, extruding the raw materials into sheets through a twin-screw extruder at 110° C. through melting, grinding the raw materials into powder through a grinder, and finally screening the powder coating through a 200-mesh sieve; spraying the powder coating onto a sample plate through an electrostatic spray gun, and curing the sample plate in an oven at 130° C. for 20 minutes.

[0031] Beneficial effects: The resin raw materials of the present invention use dibasic acid, diol, branching agent, acidolysis agent, esterification catalyst, antioxidant, and curing accelerator. By adjusting the content of thiodiglycolic acid monomer in the dibasic acid, the solid-liquid transition point temperature is less than 75.1°C. The powder coating prepared by the resin of the present invention can be cured at a low temperature of 130°C, and has good storage stability and excellent paint film leveling. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 The polyester prepared in Example 3 of the present invention is 1 H-NMR spectrum;

[0033] Figure 2a and 2b Rheological cooling curves of the polyesters prepared in Examples 1 and 6 of the present invention DETAILED DESCRIPTION

[0034] The present invention will be further described below in conjunction with the embodiments.

[0035] Example 1

[0036] Polyester resin S-0, under nitrogen atmosphere, add 245 grams of neopentyl glycol, 40 grams of ethylene glycol, 10 grams of trimethylolpropane, 1 gram of catalyst monobutyl tin oxide and 1 gram of triphenyl phosphite into the reactor, and heat to 130°C. Then add 442 grams of terephthalic acid and stir evenly. Heat to 250°C, under this reaction condition, keep warm until the reaction system is clear, then lower the temperature of the reaction system to 220°C, add 55 grams of isophthalic acid, then heat to 240°C, keep warm for 2 hours, and vacuum polycondense for 3 hours. Samples are taken for analysis of acid value and viscosity. The acid value is 26.9 mg KOH / g and the viscosity is 47.9 pa.s (180°C, 78.5 rad / s). The indicators are qualified. Add 2 grams of antioxidant tris (2,4-di-tert-butylphenyl) phosphite and 1 gram of pentaerythritol tetrapropionate, and stir for half an hour before discharging. The solid-liquid transition point was determined to be 75.1°C by rheometer.

[0037] Example 2

[0038] Polyester resin S-1, under nitrogen atmosphere, add 245 grams of neopentyl glycol, 40 grams of ethylene glycol, 10 grams of trimethylolpropane, 1 gram of catalyst monobutyl tin oxide and 1 gram of triphenyl phosphite into the reactor, and heat to 130°C. Then add 438 grams of terephthalic acid and 4 grams of thiodiglycolic acid and stir evenly. Heat to 250°C, keep warm until the reaction system is clear, then lower the temperature of the reaction system to 220°C, add 55 grams of isophthalic acid, then heat to 240°C, keep warm for 1 hour, and vacuum polycondense for 1 hour. Samples are taken for analysis of acid value and viscosity. The acid value is 35.2 mg KOH / g and the viscosity is 31.4 pa.s (180°C, 78.5 rad / s). The indicators are qualified. Add 1 gram of antioxidant tris (2,4-di-tert-butylphenyl) phosphite and 2 grams of pentaerythritol tetrapropionate, and stir for half an hour before discharging. The solid-liquid transition point was determined to be 73.8°C by rheometer.

[0039] Example 3

[0040] Polyester resin S-2, under nitrogen atmosphere, add 245 grams of neopentyl glycol, 40 grams of ethylene glycol, 10 grams of trimethylolpropane, 1 gram of catalyst monobutyl tin oxide and 1 gram of triphenyl phosphite into the reactor, and heat to 130°C. Then add 433 grams of terephthalic acid and 8 grams of thiodiglycolic acid and stir evenly. Heat to 250°C, keep warm until the reaction system is clear, then lower the temperature of the reaction system to 220°C, 55 grams of isophthalic acid, then heat to 240°C, keep warm for 1 hour, and vacuum polycondense for 1 hour. Samples are taken for analysis of acid value and viscosity. The acid value is 34.4 mg KOH / g and the viscosity is 29.4 pa.s (180°C, 78.5 rad / s). The indicators are qualified. Add 1 gram of antioxidant tris (2,4-di-tert-butylphenyl) phosphite and 2 grams of pentaerythritol tetrapropionate, and stir for half an hour before discharging. The solid-liquid transition point was determined to be 71.6°C by rheometer.

[0041] Example 4

[0042] Polyester resin S-3, under nitrogen atmosphere, add 245 grams of neopentyl glycol, 40 grams of ethylene glycol, 10 grams of trimethylolpropane, 1 gram of catalyst monobutyl tin oxide and 1 gram of triphenyl phosphite into the reactor, and heat to 130°C. Then add 429 grams of terephthalic acid and 12 grams of thiodiglycolic acid and stir evenly. Heat to 250°C, keep warm until the reaction system is clear, then lower the temperature of the reaction system to 220°C, 55 grams of isophthalic acid, then heat to 240°C, keep warm for 1 hour, and vacuum polycondense for 1 hour. Samples are taken for analysis of acid value and viscosity. The acid value is 29.8 mg KOH / g and the viscosity is 30.6 pa.s (180°C, 78.5 rad / s). The indicators are qualified. Add 1 gram of antioxidant tris (2,4-di-tert-butylphenyl) phosphite and 2 grams of pentaerythritol tetrapropionate, and stir for half an hour before discharging. The solid-liquid transition point was determined to be 68.8°C by rheometer.

[0043] Example 5

[0044] Polyester resin S-4, under nitrogen atmosphere, add 245 grams of neopentyl glycol, 40 grams of ethylene glycol, 10 grams of trimethylolpropane, 1 gram of catalyst monobutyl tin oxide and 1 gram of triphenyl phosphite into the reactor, and heat to 130°C. Then add 424 grams of terephthalic acid and 16 grams of thiodiglycolic acid and stir evenly. Heat to 250°C, keep warm until the reaction system is clear, then lower the temperature of the reaction system to 220°C, add 55 grams of isophthalic acid, then heat to 240°C, keep warm for 1 hour, and vacuum polycondense for 1 hour. Samples are taken for analysis of acid value and viscosity. The acid value is 33.5 mg KOH / g and the viscosity is 24.30 pa.s (180°C, 78.5 rad / s). The indicators are qualified. Add 1 gram of antioxidant tris (2,4-di-tert-butylphenyl) phosphite and 2 grams of pentaerythritol tetrapropionate, and stir for half an hour before discharging. The solid-liquid transition point was measured by rheometer and was 62.2℃.

[0045] Example 6

[0046] Polyester resin S-5, under nitrogen atmosphere, add 245 grams of neopentyl glycol, 40 grams of ethylene glycol, 10 grams of trimethylolpropane, 1 gram of catalyst monobutyl tin oxide and 1 gram of triphenyl phosphite into the reactor, and heat to 130°C. Then add 420 grams of terephthalic acid and 20 grams of thiodiglycolic acid and stir evenly. Heat to 250°C, keep warm until the reaction system is clear, then lower the temperature of the reaction system to 220°C, add 55 grams of isophthalic acid, then heat to 240°C, keep warm for 1 hour, and vacuum polycondense for 1 hour. Samples are taken for analysis of acid value and viscosity. The acid value is 30.1 mg KOH / g and the viscosity is 14.2 pa.s (180°C, 78.5 rad / s). The indicators are qualified. Add 1 gram of antioxidant tris (2,4-di-tert-butylphenyl) phosphite and 2 grams of pentaerythritol tetrapropionate, and stir for half an hour before discharging. The solid-liquid transition point measured by rheometer is 55.1℃.

[0047] This embodiment shows that as the amount of thiodiglycolic acid monomer increases, the solid-liquid transition point of the polyester resin continues to decrease, and the rotational viscosity also shows a downward trend. However, when the amount exceeds 5 mol% of the total amount of carboxylic acid, the storage stability of the powder coating formulated with the resin has the risk of agglomeration.

[0048] The performance of the polyester resin synthesized by the method of the present invention can be reflected by the performance of the powder coating made. 50-60 parts of the polyester resin synthesized in the above examples 1-6 are respectively mixed with 2-4.5 parts of triglycidyl isocyanurate; 10-20 parts of titanium dioxide; 8-20 parts of barium sulfate; 1-2 parts of leveling agent; 0.5-1 part of brightener; 0.2-0.6 parts of benzoin. Weigh and mix according to the proportions in Table 1, melt extrude into sheets through a twin-screw extruder at 110°C, then grind into powder with a grinder, and finally screen through a 200-mesh sieve to make a powder coating. The powder coating is sprayed on a surface-treated (phosphating) metal plate with an electrostatic spray gun, cured at 130°C / 20min, and then various performance tests are carried out. The performance test results are shown in Table 1.

[0049] Comparative Example 7 is the existing product DM7101 of Jiangsu Damerui New Materials Co., Ltd., and its product indicators are an acid value of 32.8 mg KOH / g and a viscosity of 51 Pa.s (200° C.).

[0050] Table 1

[0051]

[0052] Figure 1 The polyester prepared in Example 3 of the present invention is 1 H-NMR spectrum. Chemical shift 3.29 is CH 2 The hydrogen on the top, 4.26 is neopentyl glycol CH 2 The hydrogen on the surface indicates that thiodiglycolic acid is synthesized into the polymer, proving that the synthesis process is effective and reliable. Figure 2a and 2b The rheological cooling curves of the polyesters prepared in Examples 1 and 6 of the present invention, the intersection of the storage modulus and the loss modulus is the solid-liquid transition point. The introduction of the alkyl sulfide main chain reduces the transition point temperature. The polyester resin has good fluidity, can promote full contact of the curing groups and increase the speed of the curing reaction, improve the wetting performance of the resin matrix to the pigment and filler, and improve the leveling performance of the coating.

[0053] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A polyester resin containing an alkyl sulfide main chain, Features: The polyester resin internal structural unit contains an alkyl sulfide main chain; the polyester resin raw materials are composed of the following components in parts by weight: 40-60 parts of dibasic acid, 30-40 parts of diol, 0.01-2 parts of branching agent, 0-5 parts of acidolysis agent, 0.03-0.2 parts of esterification catalyst, 0.01-1.5 parts of antioxidant, and 0.01-1 parts of curing accelerator; The polyester resin is a carboxyl-terminated polyester resin, and its acid value ranges from 20 to 40 mgKOH / g; The dibasic acid is a mixture of terephthalic acid and thiodiglycolic acid; the amount of thiodiglycolic acid in the total polyacid substance is higher than 0% and lower than 5%; the diol is a mixture of one or more of neopentyl glycol, ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 2-methyl-1,3-propylene glycol, 1,3-butylene glycol, 2-methyl-2,4-pentanediol, 2-ethyl-1,3-hexanediol, and 1,4-butylene glycol.

2. The polyester resin containing an alkyl sulfide main chain according to claim 1, Features: The branching agent is a mixture of one or more of trimethylolpropane, trimethylolethane, 1,2,5-pentanetriol and pentaerythritol; the acidolysis agent is a mixture of one or more of isophthalic acid, adipic acid, trimellitic anhydride and maleic anhydride; the esterification catalyst is a mixture of one or more of dibutyltin oxide, tributyltin oxide, dihydroxybutyltin chloride, stannous oxalate and monobutyltin oxide; the antioxidant is a mixture of one or more of tris(2,4-di-tert-butylphenyl)phosphite, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate and octadecylβ-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate; the curing accelerator is a mixture of triphenylphosphine, triphenylethylphosphine bromide; tetraethylammonium bromide, tetrabutylammonium bromide, tetrabutylammonium chloride and dibutyltin dilaurate.

3. The polyester resin containing an alkyl sulfide main chain according to claim 1, Features: The solid-liquid transition point temperature of the polyester resin is less than 75.1°C.

4. A method for preparing the polyester resin containing an alkyl sulfide main chain according to claim 1, Features: The following steps are involved: (1) Adding diol, branching agent, esterification catalyst and part of antioxidant into a reactor under nitrogen atmosphere; (2) Heat, then add the dibasic acid and stir evenly; (3) Heat to start the reaction, then increase the temperature and keep it warm until the reaction system is clear; (4) Lower the temperature of the reaction system; (5) Add the acidolysis agent, then increase the temperature, keep it warm and continue the reaction; (6) Take samples to analyze the acid value and viscosity. After reaching the qualified indicators, add the curing accelerator and the remaining antioxidant, stir and discharge the material.

5. The method for preparing a polyester resin containing an alkyl sulfide main chain according to claim 4, Features: In the step (2), the temperature is raised to 130°C; in the step (3), the temperature is raised to 180°C to start the reaction, and then the temperature is raised to 250°C at a rate of 10-15°C / h. At this temperature, the temperature is kept until the reaction system is clarified; in the step (4), when the acid value (AV) reaches 5-20 mgKOH / g after sampling and detection, the temperature of the reaction system is lowered to 220°C; in the step (5), the temperature is then raised to 240°C, kept for 2 hours, and the reaction is continued for 2 to 4 hours under a vacuum degree of -0.09 to -0.099 MPa. In the step (6), the acid value and viscosity are sampled and analyzed, wherein the acid value is controlled at 20-40 mgKOH / g and the viscosity is controlled at 10 to 50 Pa.s at 180°C. After the indicators are qualified, a curing accelerator and the remaining antioxidant are added, and the material is discharged after stirring for 0.5 hours.

6. A powder coating based on the polyester resin containing an alkyl sulfide main chain according to claim 1, Features: The raw materials of the powder coating are composed of the following components in parts by weight: 50-60 parts of polyester resin containing an alkyl sulfide main chain, 2-4.5 parts of triglycidyl isocyanurate, 10-18 parts of titanium dioxide, 8-16 parts of barium sulfate, 1-2 parts of a leveling agent, 0.5-1 parts of a brightener, and 0.2-0.6 parts of benzoin.

7. The powder coating according to claim 6, Features: The leveling agent is a GLP503 / 588 leveling agent, the brightening agent is an accelerator BLC701, and the benzoin is benzoyl alcohol ketone.

8. A method for preparing the powder coating according to claim 6, Features: The following steps are involved: The raw materials are mixed in a mixer, melt-extruded into sheets through a twin-screw extruder at 110°C, ground into powder through a grinder, and finally sieved through a 200-mesh sieve to obtain the powder coating; the powder coating is sprayed on a sample plate through an electrostatic spray gun, and cured in an oven at 130°C for 20 minutes.